Correlation Between Onset of Diabetes Mellitus and Nitric Oxide Levels in Patient with Type 2 Diabetes Mellitus - Theosobia Grace Orno; Mansyur Arif; Irfan Idris (Medical Laboratory Technology Journal, 2018)
Type 2 diabetes mellitus (DM) is associated with increased risk of endothelial dysfunction if it lasts a long time without control. This study aims to connect the Onset of Diabetes Mellitus (DM) with Nitric Oxide levels in patients of type 2 diabetes mellitus. The study used cross-sectional study method. The samples were 86 subjects, consisting of 38 subjects of Type 2 DM controlled and 48 subjects of Type 2 DM uncontrolled. The results of the Kruskal-Wallis statistical test showed no significant difference between the Onset of DM and Nitric Oxide levels in the categories of 4-6 years (19.4 ± 10.1), 7-9 years (17.3 ± 9.3) and 10-12 years (13.3 ± 8.5) (p=0.06). Furthermore, the Spearman correlation test revealed a negative correlation between the Onset of DM and Nitric Oxide level in patients with Type 2 DM with and without control (r =-0.217). The level of Nitric Oxide (NO) can consider as a predictor of long-term complication in patients with type 2 DM.